Peanut consumption patterns in Metro Manila - Caperig, Ma Theresa M. (1999)
A survey was conducted among households in Metro Manila to determine their consumption and attitudes towards peanut and peanut products. There were fifty respondents. Results showed that peanut butter (78%) was the most commonly used peanut product and likewise the favorite product (30%). The families ate peanuts because it was nutritious, delicious, healthy and cheap. Fattening and can cause pimples were a few of the negative feelings towards peanuts. Peanut products were usually purchased at supermarkets, wet markets, and sari-sari stores. Income passively affected the peanut consumption of the households. High or low-income families consumed more or less the same amount of peanuts and peanut products. It only differed in the forms of peanut. Women did not indulge in eating peanuts because they were concerned of their weight and physical appearance. Children liked very much sweetened peanuts and peanut butter in sandwiches. Availability of substitute commodities, preference, feelings and attitudes also affected the peanut consumption of the households.